2022
DOI: 10.1007/s00704-021-03917-1
|View full text |Cite
|
Sign up to set email alerts
|

Determination of rainy season onset and cessation based on a flexible driest period

Abstract: A fixed climatological year is generally used to determine rainy season onset and cessation. However, due to changes in climate, the fixed climatological year might not be the right basis for the onset and cessation dates estimation. This study proposes the usage of the driest period in the year to establish a flexible climatological year to determine rainy season onset and cessation dates. The driest period of a climatological year is defined as the period of 14 consecutive days, which has the lowest accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…This is consistent with findings of a study which concluded that there was high variability in rainfall characteristics such as the onset and total rainfall in Eswatini making it hard to predict the amount of rainfall to be available for crop production in a given season [34]. High rainfall variation makes it difficult to identify trends with a high degree of certainty [35].…”
Section: Extent Of Rainfall Variabilitysupporting
confidence: 89%
“…This is consistent with findings of a study which concluded that there was high variability in rainfall characteristics such as the onset and total rainfall in Eswatini making it hard to predict the amount of rainfall to be available for crop production in a given season [34]. High rainfall variation makes it difficult to identify trends with a high degree of certainty [35].…”
Section: Extent Of Rainfall Variabilitysupporting
confidence: 89%
“…Because the dry and rainy seasons are mainly defined in terms of rainfall, they vary among geographic locations, even within relatively short distances (Chang, Wang, et al, 2005b; Ferijal et al, 2022; Hamada et al, 2002; Moron et al, 2009). Based on pentad (5‐day) rainfall variation, Jakarta's climatology has been classified as A–I, which is dominated by an annual cycle and a rainy season from September to February (Hamada et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…These pools present a challenge due to their unpredictable water availability, which can vary seasonally or between years (Brendonck et al, 2010). For instance, (1) the rainy or wet period shows high levels of concentrated precipitation and represents most of the annual rainfall in the region; (2) the post-rainy period might be determined by shifts in salinity and grain size distribution in surface sediments of freshwater bodies (Ferijal et al, 2022); and (3) the drought period is marked by rising temperatures and decreased precipitation relative to normal conditions, which subsequently leads to lower availability of water or a completely dry pool (Fischer et al, 2000;Sheffield & Wood, 2012;Florencio et al, 2020). In addition, these pools are shallow, simple in physical structure, and spatially discrete.…”
Section: Introductionmentioning
confidence: 99%